Advances in theoretical and experimental methods of bubble-particle turbulent detachment in flotation - Shihao DING; Wenqing SHI; Hongji CHEN; Mengdi XU; Xiahui GUI; Yaowen XING (Meitan xuebao)
Flotation is an effective method to improve the quality of fine minerals and coal, but the separation process exhibits significant size effects. The bubble-particle detachment caused by turbulence is the main reason for the upper limit of separation particle size in flotation. To increase the upper limit of flotation size and enhance the flotation effect of coarse particles, the study of bubble-particle detachment has always been a hot and difficult point in the field. The research status of bubble-particle detachment is reviewed from three aspects: quasi-static detachment theory, turbulent detachment mechanism and experimental methods. There is now a broad consensus on the normal detachment mechanism of bubble-particle aggregates, where capillary force is the main force maintaining the stability of the bubble-particle mineralized aggregates. Bubble-particle detachment can be divided into three stages: bubble stretching process, bubble sliding process, and bubble necking process. Moreover, understanding of the bubble-particle turbulence detachment mechanism has become more systematic, with centrifugal motion of particles, variable-speed motion of bubbles, and bubble oscillation being key factors leading to detachment. In addition, the comprehensive application of experimental methods such as detachment force testing technology, high-speed dynamic photography technology, particle image velocity measurement technology and numerical simulation has created a comprehensive research framework encompassing “detachment force testing, interface behavior capture, flow field analysis, and process simulation”. This comprehensive approach has greatly promoted the development of bubble-particle detachment research to a more microscopic and deeper direction, and provided sufficient and reliable experimental guarantee for revealing the bubble-particle turbulent detachment. Finally, the development direction of bubble-particle detachment research in the future is proposed, including the construction of capillary force mathematical model under different separation angles, the mechanism of bubble-particle detachment energy induced by turbulence, and the study of multi-bubble-particle detachment mechanisms induced by multi-scale turbulent vortices. Solving these key scientific problems will not only improve detachment theory but also provide important guidance for increasing the flotation size limit and enhancing coarse particle flotation performance.